Force related parameters and laterality in junior ski jumpers - Fritz, J.; Strutzenberger, G.; Schwameder, H. (Abstract Book of the 6th International Congress on Science and Skiing, December 14 - 19, 2013 St. Christoph am Arlberg - Austria, 2013)
Among the technical skills, peak force (Fmax) and peak rate of force development (RFDmax) seem to be the most important performance determining factors in ski jumping take-off. Furthermore, it is of particular importance that both feet produce the force symmetrically at take-off in order to avoid a skewed flight path. Due to the limited number of hill jumps junior ski jumpers commonly use simulated jumps as ski jumping specific technique exercise and squat jumps for the specific strength training. The purpose of this study was to analyze how useful simulated jumps and squat jumps might be for ski jumping specific "dryland" training and in which situation (static or dynamic) the biggest literalities would appear.